Exercise and caloric restriction improve cardiovascular and erectile function in rats with metabolic syndrome - ŞENER, TARIK EMRE; ŞENER, GÖKSEL (My University, 2020)
The aim of this study is to examine the possible benefits of exercise and caloric restriction (CR) on cardiovascular hemodynamics, erectile function, and antioxidant system in metabolic syndrome (MS). Sixty male Spraque-Dawley rats were divided into five groups; control, MS, MS + CR, MS + exercise (EXC), and MS + CR + EXC. To induce MS, 10% fructose solution was applied for 3 months. Thereafter, in CR groups calorie was restricted 40% and in EXC groups swimming was performed for 6 weeks. Body weight, blood glucose, and blood pressure (BP) levels were measured before and after MS induction and at the end of the experiment. After decapitation, tumor necrosis factor (TNF)-α, adiponectin (ADP), and plasminogen activator inhibitor (PAI)-1 levels were investigated in blood, oxidative stress parameters were examined in heart, aorta, and corpus cavernosum (CC) tissues. Isometric contraction in isolated tissue bath was studied in aorta and CC tissues. Animals subjected to exercise and CR had decreased BP and blood glucose levels. Impaired contraction-relaxation responses in MS group were improved with exercise and CR. MS-induced increase in TNF-α, PAI-1, malondialdehyde (MDA), and decrease in ADP, glutathione (GSH), and superoxide dismutase (SOD) were normalized with exercise and CR. Exercise and CR may be beneficial against changes in cardiovascular hemodynamics caused by MS.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology